Role of Wnt signaling pathway in joint development and cartilage degeneration - Li, Xinyan; Han, Yuanyuan; Li, Guimiao; Zhang, Yingze; Wang, Juan; Feng, Chen (Frontiers in Cell and Developmental Biology, 2023)
Osteoarthritis (OA) affects approximately 500 million people worldwide. However, no effective treatment is available to stop or delay the degenerative progression of the joints. Wnt signaling pathway plays a major role in the regulation of growth, development, and homeostasis of articular cartilage. In this review, we summarized the role of Wnt pathways in both joint development at embryonic stage and cartilage maintenance during adult life. Especially, aberrant mechanical loading has been identified to play a major role in OA progression. Excessive mechanical load will induce activation of Wnt pathway in chondrocytes, resulting in chondrocyte apoptosis, matrix destruction and other osteoarthritis-related changes. Finally, a discussion of diverse emerging Wnt-related modulators is conducted, and an overview of emerging treatments of OA targeting Wnt signaling is presented. This review will provide us with clues to find new drugs or gene therapies targeting Wnt signaling pathway for the diagnosis and treatment of osteoarthritis and other degenerative joint diseases.